Corrosion inhibition and adsorption behavior of 5-(Phenylthio)-3H-pyrrole-4-carbonitriles on mild steel surface in 1M H2SO4: Experimental and computational approach - Verma C.; Quraishi M.A.; Korde R. (My University, 2025)
Present study describes the effect of electron donating hydroxyl (-OH) group (s) on adsorption behavior of three 5-(phenylthio)-3H-pyrrole-4-carbonitriles (PPCs) on mild steel corrosion in 1 M H2SO4 using gravimetric, Tafel polarization and impedance spectroscopy (EIS), quantum chemical calculations and molecular dynamics simulations methods. The inhibitors showed the maximum efficiency of 91.32%, 92.97% and 94.62% for PPC-I, PPC-II and PPC-III, respectively at 1.29×10-4 mol/L concentration and behaved as mixed type inhibitors. Adsorption of studied inhibitors on mild steel surface followed the Langmuir adsorption isotherm. The quantum chemical calculation parameters such as EHOMO, ELUMO, ΔE, global harness, softness, electronegativity and fraction of electron transfer (DN) were calculated using DFT method to correlate the electronic properties with the adsorption behavior of studied molecules. The adsorption behavior of the inhibitor molecules was further supported by their adsorption energies using molecular dynamics simulations method. © 2016 by CEE (Center of Excellence in Electrochemistry).